GEOCHEMICAL DIFFERENTIATION OF SPHEROIDAL RHYOLITE FROM THE REGION NORTH OF THE SEA OF OKHOTSK - Gundobin G.M.; Paradina L.F. (My University, 1987)
The authors investigated spheroidal rhyolite samples from the Paren' volcanic field in the Evensk zone of the Okhotsk-Chukotka belt. The Upper Cretaceous volcanic sequence here is dominated by latite-andesite and andesite-basalt lavas and subordinate ignimbrites. Granitoid intrusions were injected in the closing stage of Late Cretaceous igneous activity. The internal structure of spheroids is concentrically rhythmic. Thus, rhythms composed essentially of albite alternate with those of quartz and potassic feldspar. It is shown that spheroids are richer in sodium and aluminum and lower in silicon, potassium and magnesium than the matrix, a trend consistent with their domination by 'albite' rhythms. They also are lower in boron but have a higher K/Rb ratio. The matrix is close in composition to 'K-spar' rhythms but contains somewhat more silicon and sodium.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая